The Effect of Using Peer-Assisted Learning Strategy toward Students’ Reading Comprehension at SMKN 1 Tanjung Raya - Rama Wahyu Utama; Jufri Jufri (Journal of English Language Teaching, 2019)
This is quasi experimental research by using quantitative approach which is aimed to investigate the effect of using PALS toward reading comprehension.  The writer used test in form of multiple choice to collect the data. The population of the research was 55 students of the tenth grade students at SMKN 1 Tanjung Raya and the sample was X TITL 1(25 students) as control grup  and X TKJ 1(30 students) as experimental class with PALS. To determine the sample, the writer used cluster sampling. In order to analyze the data, the writer used the normality test by using Liliefors test and tested the homogeneity of the data by using f test. The writer used z test formula to test the hypothesis and consulted its result with the z table with a = 0.05. The result of this research showed that the hypothesis was accepted. It showed that Tobtained > Ttable or 2.14 > 1.645. So, the reading comprehension of the students who were taught with PALS better than the students who were taught without PALS.